2016
DOI: 10.3389/fmicb.2016.00046
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Capabilities of Microorganisms Involved in and Associated with the Anaerobic Oxidation of Methane

Abstract: In marine sediments the anaerobic oxidation of methane with sulfate as electron acceptor (AOM) is responsible for the removal of a major part of the greenhouse gas methane. AOM is performed by consortia of anaerobic methane-oxidizing archaea (ANME) and their specific partner bacteria. The physiology of these organisms is poorly understood, which is due to their slow growth with doubling times in the order of months and the phylogenetic diversity in natural and in vitro AOM enrichments. Here we study sediment-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 98 publications
10
114
0
Order By: Relevance
“…The physiology in that case may be interpreted to operate non-syntrophically, since the amount of energy from sulfate reduction would obviate the need for a syntrophic partner (62). It is not clear how widespread archaeal sulfate reduction with methane is however, since subsequent investigations (108, 109) reported that dominant SRB partner organisms did not grow on elemental sulfur as proposed and microcosm-derived SRB did not have the ability to disproportionate sulfur at the 7:1 stoichiometry of sulfide and sulfate, as previously reported (62). …”
Section: Methanogen or Methanotroph? Follow The Electronsmentioning
confidence: 81%
See 1 more Smart Citation
“…The physiology in that case may be interpreted to operate non-syntrophically, since the amount of energy from sulfate reduction would obviate the need for a syntrophic partner (62). It is not clear how widespread archaeal sulfate reduction with methane is however, since subsequent investigations (108, 109) reported that dominant SRB partner organisms did not grow on elemental sulfur as proposed and microcosm-derived SRB did not have the ability to disproportionate sulfur at the 7:1 stoichiometry of sulfide and sulfate, as previously reported (62). …”
Section: Methanogen or Methanotroph? Follow The Electronsmentioning
confidence: 81%
“…In the case of ANME-1-targeted experiments, SRB partners were shown to decouple growth from their archaeal syntrophic partners when H 2 was supplied (108). However, H 2 appears to only decouple in the case of thermophilic consortia and not in their mesophilic relatives, and this may explain why previous studies failed to observe effects with H 2 (60, 66, 67, 109). In the case of de-coupling through an added electron acceptor, a number of soluble electron acceptors have been used to demonstrate that methane oxidation by marine ANME-2 can be de-coupled from bacterial partners (84).…”
Section: Methanogen or Methanotroph? Follow The Electronsmentioning
confidence: 91%
“…Alternatively, members of ANME−SRB consortia might themselves engage in the production of methane rather than in sulfate-coupled AOM, as previously suggested (51)(52)(53)(54)(55). Recent experiments on the methanogenic potential of ANME-1 and ANME-2 enrichment cultures, however, have not supported this idea (59). A minor amount of methane was detected in our N 2 -containing #3730 and #7136-37 microcosms; however, these levels were similar to concentrations measured as a trace contaminant in the N 2 tank (∼1-10 ppm methane).…”
Section: Hpg Amendment Had No Detectable Effect On Microbial Communitymentioning
confidence: 96%
“…In two cases, researchers were successful [23, 100]. In one of these cases, sediment-free long-term AOM enrichments that were dominated by ANME/SRB were incubated with methanogenic substrates.…”
Section: Reversal Of the Methanogenesis Pathwaymentioning
confidence: 99%
“…In one of these cases, sediment-free long-term AOM enrichments that were dominated by ANME/SRB were incubated with methanogenic substrates. The resulting methanogenic activity most likely came from the enrichment of a minor population of methanogens (up to 7‰ of total archaeal gene tag sequences) that was present in the inoculum [100]. In the second study, methanogenic substrates were added to ANME-1 and ANME-2 dominated microbial mat samples and methanogenesis also occurred [23].…”
Section: Reversal Of the Methanogenesis Pathwaymentioning
confidence: 99%